Hypersensitivity to carbamazepine presenting as pseudolymphoma. Issue 11 (November 1986) - Yates, P; Stockdill, G; McIntyre, M
Abstract : An unusually severe hypersensitivity reaction to carbamazepine is described, in which the patient presented with lymphadenopathy, hepatosplenomegaly, bone marrow suppression, immunosuppression and other features strongly suggestive of a lymphoma.